Pengaruh Terapi Refleksi Kaki terhadap Kualitas Tidur Pasien Kanker Payudara yang Menjalani Kemoterapi - Andriani, Zilya; Gayatri, Dewi Gayatri; Waluyo, Agung (Journal of Telenursing (JOTING), 2024)
ABSTRACT This study aims to investigate and analyze the effectiveness of foot reflexology therapy on the sleep quality of breast cancer patients undergoing chemotherapy. The method used was a literature search across four databases, namely ScienceDirect, Scopus, ProQuest, and Sage Journals, based on the PICO framework. The research design identified included nine articles employing the Randomized Controlled Trial (RCT) method and one article with a case report design. The study results indicate that foot reflexology as a non-pharmacological intervention is effective in improving the sleep quality of cancer patients, particularly breast cancer patients undergoing chemotherapy. In conclusion, foot reflexology can be used as an effective complementary therapy to improve the sleep quality of cancer patients and may be combined with other therapies. Keywords: Breast cancer, Foot reflexology, Sleep quality